Interrogating Community Self-Help Development Initiatives in Ikpoba Okha and Oredo Local Government Areas, Edo State, Nigeria - Okonmah, Emmanuel Ifechukwude; Mustapha, Adesoye Isiaka; Ovenseri, Abel Enoguanmwonsa (NIU Journal of Humanities; Vol 7 No 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022DO - 10.58709/niujhu.v7i2.1469, 2022)
This paper interrogates community self-help development initiative to ascertain the complementary roles the local governments in line with their constitutional mandates can play in strengthening local efforts in addressing felt needs. To achieve this, it raised some research questions and adopted the survey research design. Using a multistage sampling, it elicited responses through questionnaires and in-depth interviews on the phenomenon being investigated from residents of Amagba community in Oredo and Idogbo community in Ikpoba Okha Local Government Areas in Edo State. Data were analysed using the simple percentages and thematisation. Findings reveal that although community self-help initiatives such as the provision of security, electricity, pipe-borne water, community layouts mapping, roads and drainages promote development, these initiatives mostly lack Local Government support thereby leading to unintended consequences like flooding, erosion and urban slums. To be assured of quality and sustainable delivery of community self-help development initiatives, it recommends that the Local Governments need to strengthen its funding, technical and supervisory capacities as well as set up a special department for the coordination of community self-help initiatives so as to reposition the Local Governments as effective enablers of community developmental efforts. Keywords : Community, Self-help initiatives, Local government, Development